1999
DOI: 10.3171/jns.1999.91.6.1020
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of increased exposure resulting from orbital rim and orbitozygomatic osteotomy via the frontotemporal transsylvian approach

Abstract: Significant and consistent increases in surgical exposure were obtained by using orbital osteotomy, whereas zygomatic arch removal produced less consistent gains. Both maneuvers may be expected to improve surgical access. However, because larger and more consistent gains were afforded by orbital rim removal, the threshold for removal of this portion of the orbitozygomatic complex should be lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 30 publications
3
74
0
2
Order By: Relevance
“…Several authors have advocated mobilizing the zygomatic arch by performing a simple zygomatic osteotomy or using extended frontotemporo-orbitozygomatic approaches to reach low-lying lesions. [1][2][3] Intraoperative neuromonitoring (IOM) is one of the methods in which modern neurosurgery can improve surgical results while reducing morbidity. Motor-evoked potentials (MEPs) obtained by transcranial electrocortical stimulation is routinely used to monitor major motor pathways intraoperatively during several neurosurgical procedures.…”
mentioning
confidence: 99%
“…Several authors have advocated mobilizing the zygomatic arch by performing a simple zygomatic osteotomy or using extended frontotemporo-orbitozygomatic approaches to reach low-lying lesions. [1][2][3] Intraoperative neuromonitoring (IOM) is one of the methods in which modern neurosurgery can improve surgical results while reducing morbidity. Motor-evoked potentials (MEPs) obtained by transcranial electrocortical stimulation is routinely used to monitor major motor pathways intraoperatively during several neurosurgical procedures.…”
mentioning
confidence: 99%
“…3,[10][11][12][13][14][15] The quantitative interpretations of these surgical procedures, which intend to ''extend'' the exposure of the standard pterional craniotomy, are much in vogue now. 4,5,13 Schwartz et al 5 used a frameless stereotactic system to measure the area of exposure associated with removal of the orbital roof compared with the zygomatic arch. They sequentially performed a frontotemporal craniotomy (inclusive of removing the entire greater sphenoid wing), then removed the superior and lateral walls of the orbit, followed by resection of the zygomatic arch.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, in a study using human cadavers, Schwartz et al have suggested that removal of the lateral orbital rim alone may be sufficient to reach many of these same targets for which the orbitozygomatic craniotomy has been used. 5 But their study did not address the more important ''angle of attack.'' Also, their surgical window, defined as being 10 cm from the anatomic structures, did not represent the actual working space under the microscope.…”
mentioning
confidence: 99%
“…The superior viewing angle to the top of the third ventricle is also limited, although it is somewhat improved with an orbitozygomatic approach. 15,25,33 In addition, access to the interpeduncular cistern and infrachiasmatic region through the optico-carotid and carotidoculomotor corridors can be narrow and is sometimes obstructed by perforating arteries.…”
Section: Choice Of Surgical Approachmentioning
confidence: 99%